Exploring the Essential Word Lists for Engineering Education: Engaging the Vocabulary Profiling Approach (VPA) - Ng Y.J.; Chong S.T.; Ng P.K.; Yeow J.A.; Ismail L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Engineering education; Engineering keyword; Engineering vocabulary profiling; Engineering words; English as second languages; Essential engineering word list; Learn+; Lexical coverage; Text comprehensions; The language of engineering; Word lists; Students